Inovasi Anamnesis Berbasis Platform Digital: Solusi Menurunkan Angka Serangan Jantung dan Henti Jantung - Rumansara, Leddy Naomi; Watofa, Yosefina Marijke; Rusman, Nuraliah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Heart disease remains a leading cause of death worldwide and continues to pose a major public health challenge, including in Jayapura City. Low awareness of risk factors and limited access to health services lead to late detection of cardiovascular conditions. This community service project aimed to develop a digital platform-based anamnesis innovation as an early screening tool for heart disease. Using a Google Form consisting of 21 questions about risk factors, symptoms, and medical history, 38 participants independently completed the screening. Results showed that 94.7% of respondents had a history of smoking and 65.8% had metabolic risk factors such as obesity or diabetes, while 92.1% had never undergone echocardiographic examination. The use of this digital platform facilitated the anamnesis process, enhanced participants’ awareness of risk factors, and encouraged preventive behavior. This innovation is expected to contribute to reducing the incidence of heart attacks and cardiac arrests through improved early detection and digital-based health education.